Primary Spontaneous Pneumomediastinum: Case Report - Adadioglu, Ismail; Yavuz, Yucel; Solak, Okan; Yurumez, Yusuf; Esme, Hidir (Emergency Medicine Physicians Assoc Turkey, 2010)
Introduction: Spontaneous pneumomediastinum, without any triggers cause or trauma is described as finding air in the mediastinum and this is a rare clinical situation. Case report: Our emergency room, said to be close by psychological problems brought the feeling of congestion in the throat, inability to breathe and chest pain complaints, which present a case with the diagnosis of spontaneous pnmomediastinum. Conclusion: systemic examination is very important in conversif reactions. In the differential diagnosis of chest pain and dyspnea, spontaneous pneumomediastinum should always be considered.
Keywords: Pneumomediastinum; Conversif Reaction; Chest Pain; Dispne